Effect of High- Fiber Diet alongside with Aerobic Exercise on HbA1c, Fasting Blood Glucose and BMI of Overweight Diabetic Women - Saeed Keshavarz; Narges Eslahchi; Ebrahim Pourhakimi; Mohammad Karimi (Islamic Azad University, 2016)
Introduction: New lifestyle is one of the most important causes of increased prevalence of diabetes due to inappropriate nutrition, consecutive stress, and lack of physical activity. The aim of this study was to investigate the effect of high- fiber diet and aerobic exercise on fasting blood glucose, HbA1c, and BMI in diabetic overweight women. Methods: 41 overweight females with type 2 diabetes (aged between 40- 60) were selected to participate in the study. Patients were randomly divided into four groups including (control, high-fiber diet, aerobic exercise, and high-fiber diet+ aerobic exercise). The high fiber diet group consumed 25-30 gr fiber daily during 12 weeks. The aerobic exercise intensity was 60% of maximum heart rate, and each session took 20- 45 minutes (every two weeks 5 minutes was added). High-fiber diet + exercise group did the aerobic exercises, in addition to receiving 25-30 gr fiber in a day. The control group had no regular exercise activities or a special diet. Fasting blood sugar (FBS) samples were taken before and after the test. Data was analysed by Mann-Whitney U-test and Covariance analysis tests. Results: The results of the study showed a significant reduction in HbA1c in the exercise group and in the high- fiber diet + exercise group compared to the control group (p=0.001). There were no significant differences in fasting blood glucose in the experimental groups compared to the control group (p=0.482). BMI changes were significantly higher in both control, and high- fiber diet + exercise groups (p=0.050). Conclusion: The findings of the present study showed that aerobic exercise can solely or combined with a high-fiber diet relieve the chronic symptoms of diabetes. Also, BMI could have a significant decrease due to exercise and high-fiber diet. As a result, it seems that a regular exercise program and a high-fiber diet can be a part of prevention and treatment of diabetes.